Comparative Evaluation of Efficacy of Chlorhexidine and Herbal Mouthwash as a Preprocedural Rinse in Reducing Dental Aerosols: A Microbiological Study - Sangeeta Umesh Nayak; Anushka Kumari; Valliammai Rajendran; Vijendra Pal Singh; Ashwini Hegde; Keshava K. Pai (International Journal of Dentistry)
Objective. The risk to dentists, assistants, and patients of infectious diseases through aerosols has long been recognized. The aim of this study was to evaluate and compare the efficacy of commercially available preprocedural mouth rinses containing 0.2% chlorhexidine (CHX) gluconate, Befresh™ herbal mouthwash, and water in reducing the levels of viable bacteria in aerosols. Materials & Methods. This was a single-center, double-masked, placebo-controlled, randomized, three-group parallel design study. 30 patients (10 patients in each group) were recruited in the study. Patient rinsed mouth with 10 ml of CHX, 10 ml Befresh™, or 10 ml water. All the patients underwent supragingival ultrasonic scaling for a minimum of 30 min. The aerosol collection was done using a blood agar plate. The blood agar plates were kept approximately 12 inches from the patient’s mouth. The microbial culture was analyzed. The colony-forming unit (CFU) counting in all three groups was assessed using one-way ANOVA test to compare among the groups (p value <0.001). The intergroup comparison was done using the post hoc Tukey test. Result. There was a marked reduction in the CFU in the CHX group in all three areas. This was followed by Befresh™ (Sagar Pharmaceuticals) mouthwash. There was no reduction in the CFU of the water group. Conclusion. This study proves that a regular preprocedural mouth rinse could significantly reduce the majority bacteria present in aerosols generated by the use of an ultrasonic unit, and Befresh™ mouth rinse was found to be equally effective in reducing the aerosol contamination to 0.2% CHX gluconate.